Rancangan Teknis Penambangan dan Penjadwalan Produksi Jangka Pendek (Short Term Scheduling) pada Penambangan Bijih Nikel PT. Gerbang Multi Sejahtera - Aprilia, Aprilia; Rembah, Rina; Nurfasiha, Nurfasiha (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2024)
Block U8 is one of the front of PT. Gerbang Multi Sejahtera which is still virgin condition with an area 14,5 ha. The aim of this research is to estimate reserves, design mining techniques, and make production cheduling based on the design result. The data needed in this research is drill logs. Data from the result of estimating laterite nikel reserve using the Kriging method using Surpac 6.5.1 software shows that the one tonnage is 1.063.919 tons with an average Ni content of 1,80%. The tier geometry used is in accordance with the company’s geotechnical records, namely a tier height of 5 m, a tier depth of 2 m and a single tier slope of 50o. The width of the haul road on a straight road is 12,63 m dan the width of the haul road on bends is 13,97 m, the road grade used is 12%. The planned mining method is open pit which is divided into 3 sequences and consists of 21 ming pushback with a minr life 21 month. The need for Excavator Doosan DX 200A must-dig tools for the progress of the mine from the 1st moth to the 21st month are constant. 1 unit OB digging tool, 1 unit of Ore digging tool, and 1 unit of mush material Ore. The mean of transportation killed were 3 unit in Pit 1 and Pit 2, while in Pit 3 it was 4 units.